Survival of pacific salmons in the North Pacific in winter-spring season - Svetlana V. Naydenko; Olga S. Temnykh (Известия ТИНРО)
Influence of several factors (water temperature, food supply, predatory, size of juveniles) on pacific salmons survival during wintering is considered on the data collected from the upper pelagic layer in surveys conducted by Pacific Fisheries Research Center (TINRO) in the North-West Pacific. There is highly unlikely that the temperature influences on fish mortality directly. There is no obvious proof of negative influence of the low temperature on food base of salmons, as well. The lowering of forage zooplankton biomass in the Subarctic Front zone in February-March is insufficient for the salmons starvation taking into account that the total abundance of planktivorous nekton is also lowered in this area and generally in the Subarctic waters in winter-spring, so the food supply cannot be considered as a crucial factor of the salmons survival. Seasonal changes with lowering of feeding intensity, lipid accumulation, and somatic growth in winter known for pacific salmons aren’t forced by poor food base but are a feature of their species-specific life strategy with cyclic changes of metabolism. Predators are not abundant in the Subarctic zone in winter, so the predatory also cannot cause the high mortality of salmons. Relationship between the size of juveniles and their mortality in winter is considered in detail for the Okhotsk Sea stocks of pink salmon and there is concluded that the size of juveniles cannot be a predictor of their year-classes return for spawning. Thus, any single factor doesn’t determine winter mortality of pacific salmons but their survival is likely determined by a complex interaction of abiotic and biotic factors.